A Case-Control Study for the Effectiveness of Oral Zinc in the Prevention and Mitigation of COVID-19 - Gordon, Antonio M.; Hardigan, Patrick C. (Frontiers in Medicine, 2021)
Background: The ongoing coronavirus disease-19 (COVID-19) pandemic (caused by an infection with severe acute respiratory syndrome (SARS)-coronavirus (CoV-2) has put a burden on the medical community and society at large. Efforts to reduce the disease burden and mortality over the course of the pandemic have focused on research to rapidly determine age-stratified seroepidemiologic surveys, a centralized research program to fast-track the most promising rapid diagnostics and serologic assays, and the testing of potential anti-viral agents, immunologic therapies, and vaccine candidates. Despite the lack of official recognition for the role of nutrition in the fight against COVID-19 infection, multiple groups proposed zinc supplementation as an adjuvant for the management of participants. Method: In an ambulatory, interventional, prospective, single-blind study, we evaluated the effectiveness of zinc supplementation in the prevention and mitigation of COVID-19 in two similar participant groups. In Clinic A (n = 104) participants were randomized to receive 10 mg, 25 mg, or 50 mg zinc picolinate daily, and Clinic B control participants paired according to their demographics and clinical parameters (n = 96). All participants were compared based on demographics, clinical comorbidities, blood counts, renal functions, vitamin D levels, and their development of symptomatic COVID-19 infection. Results: Symptomatic COVID-19 infection was significantly higher among the control group participants (N = 9, 10.4%) than the treatment participants (N = 2, 1.9%), p = 0.015. The unadjusted odds ratio indicates that symptomatic COVID-19 infection was 5.93 [95% CI: 1.51, 39.26] higher in the control group, p < 0.01. Controlling for co-morbidities, individuals in the control group were 7.38 (95% CI: 1.80, 50.28) times more likely to develop symptomatic COVID-19 infection as compared with individuals in the treatment group (p < 0.01). For every-one unit increase in the number of co-morbidities, the likelihood of developing symptomatic COVID-19 infection increased 1.57 (95% CI: 1.16, 2.19) (p = 0.01). Discussion: The findings from our study suggest that zinc supplementation in all three doses (10, 25, and 50 mg) may be an effective prophylaxis of symptomatic COVID-19 and may mitigate the severity of COVID-19 infection. Conclusion: Zinc is a relatively inexpensive mineral nutrient that is an effective prophylactic agent to prevent and mitigate the potentially deadly symptomatic SARS-CoV-2 infection. As the COVID-19 pandemic continues with a lag in vaccinations in some regions and the continued emergence of dangerously infectious variants of SARS-CoV-2, it is important to replicate our data in other populations and locations and to engage public health and nutrition services on the emergent need to use zinc supplantation or fortification of staple foods in the prevention and mitigation of COVID-19 infection severity.